Korelasi Ukuran-Ukuran Tubuh Dengan Bobot Badan Kambing Lakor Jantan Muda - Lodia Aleda Tetletlora; Rajab Rajab; Godlief Joseph (Faculty of Agriculture, Musamus University, 2023)
Analysis of body sizes in ruminant livestock is very important for selecting superior animals, and if used properly in goat farming, the result can increase the success of goat production. This study aims to evaluate the correlation between body size and body weight of Lakor goats. A total of 60 male Lakor goats aged 1-2 years were randomly selected as research samples to be observed and measured. The variables observed were body weight, body length, chest circumference, shoulder height, and chest depth. The relationship between body weight and body size of goats uses correlation analysis and simple linear regression. The research results of body length, chest circumference, shoulder height, and chest depth have a correlation with body weight of 0.97 (very strong), 0.76 (strong), 0.88 (very strong), and 0.22 (low ). It can be concluded that body length can be used to estimate the body weight of Lakor goats.